The social participation of workers in the national workers’ health policy: Construction process, advances and challenges - Carvalho, Tatiana Ferraz; Paula, Elaize Maria Gomes de; Araújo, Ana Cláudia de Melo; Alves, Matheus Henrique Souza; Ribeiro, Gabriel Vieira; Carvalho, Letícia Alves (Seven Editora, 2024)
Workers' Health (WHS) policies in Brazil have a history marked by advances and setbacks, where the country has made significant progress in building a universal health system (SUS), and which includes WTS as one of its priorities. . There are still many challenges to be overcome, such as lack of resources, inadequate decentralization and resistance from business sectors. OBJECTIVE: To expand knowledge about the field of ST in Brazil and verify whether there has been progress in its implementation in Brazil and what challenges still need to be faced for its full consolidation. METHODOLOGY: The method of this study was an integrative literature review (RIL), with research carried out in the SciELO and Lilacs databases , with a total of 8 articles. RESULTS: The articles that were part of this study highlight the advances, challenges and perspectives for the future of ST. Regarding advances, we have the approval of the National Workers' Health Policy (PNST) in 2011, which established the guidelines for AIST in Brazil, the creation of the National Workers' Health Surveillance System (SINAN-T) , in 2015, and the implementation of ST programs in some states and municipalities. In relation to the challenges, it is worth highlighting the lack of financial, human and technological resources; lack of coordination of ST between the different sectors; lack of worker participation. FINAL CONSIDERATIONS: To overcome these challenges, there needs to be a joint effort between the government, workers and companies in addition to strengthening the decentralization of this policy. DOI:https://doi.org/10.56238/sevened2024.006-032